2015
DOI: 10.1016/j.neuropharm.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CB2 receptor is required for the therapeutic effect of ABHD6 inhibition in experimental autoimmune encephalomyelitis

Abstract: Alpha/beta-hydrolase domain 6 (ABHD6) is a novel 2-arachidonoylglycerol (2-AG) hydrolytic enzyme, that can fine-tune the endocannabinoid signaling in the central nervous system. Recently we and others have demonstrated the protective effect of ABHD6 inhibition in the animal models of traumatic brain injury and epileptic seizures. In this study, we investigated the role of targeting ABHD6 in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS). Post-symptom treatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 70 publications
2
79
0
1
Order By: Relevance
“…Before addition to the enzyme-linked immunoassay (EIA), the medium was centrifuged at 5000 rpm for 2 min with a table top centrifuge to exclude residual cells. To determine the role of WWL70 on PGE 2 production in vivo, EAE was induced by subcutaneous injection of myelin oligodendrocyte glycoprotein peptide 35–55 (MOG 35–55 ) in 8-week-old female C57BL/6 mice, and the clinical score was assessed as we reported recently [23]. WWL70 (10 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before addition to the enzyme-linked immunoassay (EIA), the medium was centrifuged at 5000 rpm for 2 min with a table top centrifuge to exclude residual cells. To determine the role of WWL70 on PGE 2 production in vivo, EAE was induced by subcutaneous injection of myelin oligodendrocyte glycoprotein peptide 35–55 (MOG 35–55 ) in 8-week-old female C57BL/6 mice, and the clinical score was assessed as we reported recently [23]. WWL70 (10 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…The resultant mixture was applied to a prostaglandin EIA to measure the total amount of prostaglandins including PGE 2 and PGF 2α . The PGE 2 biosynthesis assay was performed using microsomes derived from BV2 cells treated with LPS for 8 h or brain tissue from EAE mouse at day 21 post-immunization [23]. BV2 cells were suspended with 0.1 M potassium phosphate (pH 7.4), 0.25 M sucrose, 1 mM β-glycerophosphate, 1 mM sodium vanadate, 1 μM MAFP, and protease inhibitor cocktail (Roche) and disrupted by sonication for 15 s, while the brain tissue was homogenized with a Potter homogenizer with the potassium phosphate buffer at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABHD6 expression negatively regulates AMPA subunit surface expression 46 , and in a mouse model of multiple sclerosis, it was found that therapeutic effects seen by ABHD6 inhibition are mediated through the activation of the CB2 receptor. 45 Overall ABHD6 is a very attractive drug target, but only a few specific inhibitor chemotypes have been identified so far, namely triazoleureas 19 , glycine sulfonamides 20 , and thiadiazole carbamates 21 . In the absence of the ABHD6 atomic structure, biochemical characterization through mutational and functional analysis is key in the continued progression and improvement in developing potent, selective ABHD6-inhibitors.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…The native fatty acids oleic acid and palmitic acid were paired with 6-methoxy-4-methylcoumarin with an ester bond and analyzed. Both palmitic and oleic acid paired with coumarin were able to be hydrolyzed by hMGL with high affinity, but 45 with a large reduction in maximal velocity; neither fatty acid was compatible with hABHD6 ( Figure 15D and 15E, Table 5). …”
Section: Optimization Of Fluorescent Substrate For Recombinant Abhd6mentioning
confidence: 99%